Legal regulation of operation of foreign capital in the Russian empire during the First world war - Степанченко, Олена Сергіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
This article analyzes the extraordinary legislation of the Russian Empire during the First World War. The author analyzes the main legal acts regulating the activities of foreign investors in Russia (1914-1917).